Pengaruh Perubahan Perilaku Afektif terhadap Perilaku Tokoh Utama dalam Anime Honzuki no Gekokujou Season 1 Karya Miya Kazuki - Dini Lutfiana Ambarwati; Hendri Zuliastutik (Faculty of Letters, Dr. Soetomo University, 2022)
This study discusses changes in affective behavior that occur in the main character in Miya Kazuki's Honzuki no Gekokujou Season 1 anime. Affective behavior is behavior related to attitudes and feelings. This study aims to describe the factors that cause behavioral changes in the monozukuri concept on behavior, and the impact of behavioral changes on the main character in Miya Kazuki's Honzuki no Gekokujou Season 1 anime. The theory used in this study is Skinner's behaviorism which states that human behavior can change due to several factors. This study uses a qualitative descriptive method with data in the form of descriptions and analytical techniques with descriptive analysis. The results of this study found internal and external factors. Internal factors found 4 data and external factors found 3 data. The concept of monozukuri found 2 data. The impact of behavior change is found in 2 data, namely the impact on one self and the impact on others. Changes in behavior in the main character make him more independent, more compassionate, independent, innovative, and creative Keywords: anime; behavior change; Honzuki no Gekokujou Season 1.